Language attitudes of Kadazandusun people toward their mother tongue - Lydia, Tumin. (Universiti Malaysia Sarawak, UNIMAS, 2008)
The study seeks to investigate language attitudes of Kadazandusun people toward their own language, which is the Kadazandusun language. It also sought to examine respondents’ language proficiency in Kadazandusun, language used in interaction across generations in the 50 selected families and the language used in different domains. The study was undertaken in one Kadazandusun dominant community in Keningau, Sabah. Data were gathered through questionnaire. Participants were made up of 90 Kadazandusun, aged 14 years to 65 from the 50 selected families in this community. All data were calculated based on age variable wherever necessary. The study found that, majority of the respondents, possessed positive attitudes toward the Kadazandusun language regardless of age. The language proficiency has decreased among younger generation. Data on language use in the families demonstrated the differences in language used between older and younger generation, with Kadazandusun was preferable among older generation and Malay language was favored by the younger generation. Findings in domains analysis show that Kadazandusun language was used more in three domains namely workplace, neighborhood and friendship domains. Malay language on the other hand was used more in four domains, which were in religion, education, transaction, and family domains.